Estimation of sensitiveness to antimicrobial preparations of clinical strains of Esсherichia coli - Voyda, Y (Annals of Mechnikov’s Institute, 2020)
High prevalence of drug-resistance among the isolates – representatives of normal microflora is set which does them the potential source of distribution of determinants of drug-resistance among population of this species and family species of bacteria of different taxonomical groups. The high sensitiveness of strains of E. coli to imipenem, gatifloxacin and amikacin is set, that determines their practical value as preparations of reserve for treatment of infections caused by strains with multidrug-resistance. It is found out the growth of resistance to fluoroquinolones and circulation of generous amount mildly proof strains to the nitroxolinum and derivatives of nitrofuran, which occupy a leading place in the charts of the empiric therapy of patients by the chronic infections of urinoexcretory ways.